Outcome of the Glenn procedure as definitive palliation in single ventricle patients. (15th March 2020) - Vermaut, Astrid; De Meester, Pieter; Troost, Els; Roggen, Leen; Goossens, Eva; Moons, Philip; Rega, Filip; Meyns, Bart; Gewillig, Marc; Budts, Werner; Van De Bruaene, Alexander
Abstract: Objectives: In selected single ventricle patients, a Glenn procedure (SV-Glenn) may be considered as definitive palliation. Either the patient is unsuited to progress to a Fontan circulation or a SV-Glenn circulation is preferred. This study aimed at describing the clinical course, and long-term mortality/morbidity of SV-Glenn patients. Methods: All SV-Glenn patients followed at the University Hospitals Leuven before May 2018 were included. Patients who underwent, or were awaiting, TCPC completion and those who underwent a Glenn in the setting of a biventricular circulation one-and-a-half repair (OAHR), were excluded. Results: Of 65 Glenn-only patients identified, 21 (32%) had OAHR, whereas 44 (68%) were SV-Glenn patients. Of SV-Glenn patients, 19 died within 6 months after the Glenn procedure. Of 25 SV-Glenn survivors, median age at Glenn was 6.3 (IQR 1.2–29.7) years. Eight were unsuited for TCPC completion; in 17 SV-Glenn was preferred over TCPC completion. Over a median follow-up time of 11 (IQR 3–18) years after the Glenn procedure, 5 (20%) patients died. At latest follow-up 10 (40%) had heart failure, 5 (20%) had atrial and 4 (16%) ventricular arrhythmias, 2 (8%) a thromboembolic event, 7 (28%) required pacemaker implantation, and 2 (8%) had infective endocarditis but none developed cirrhosis or protein-losing enteropathy. Mean saturation at latest follow-up was 87 ± 7%. Conclusion: SV-Glenn patients represent a unique and heterogeneous patient population. Outcome was reasonable, although comorbidities, such as heart failure and arrhythmias were not uncommon. In SV-Glenn patients, 'classic' complications related to Fontan physiology, such as cirrhosis and protein-losing enteropathy, were absent. Highlights: SV-Glenn patients represent a heterogeneous population. Medium-to-long term mortality is reasonable. Comorbidities in SV-Glenn patients are not uncommon. Glenn palliation in adulthood is feasible.